2010
DOI: 10.1186/1471-2229-10-221
|View full text |Cite
|
Sign up to set email alerts
|

Global transcript profiling of transgenic plants constitutively overexpressing the RNA-binding protein AtGRP7

Abstract: BackgroundThe clock-controlled RNA-binding protein AtGRP7 influences circadian oscillations of its own transcript at the post-transcriptional level. To identify additional targets that are regulated by AtGRP7, transcript profiles of transgenic plants constitutively overexpressing AtGRP7 (AtGRP7-ox) and wild type plants were compared.ResultsApproximately 1.4% of the transcripts represented on the Affymetrix ATH1 microarray showed changes in steady-state abundance upon AtGRP7 overexpression. One third of the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 63 publications
4
55
0
Order By: Relevance
“…Microarray analyses revealed that ectopic overexpression of GRP7 affects the steady-state abundance of a suite of cellular transcripts. Among those are circadian-regulated transcripts and transcripts influenced by abiotic and biotic stress (66). Because GRP7 interacts with translational machinery components it is likely that GRP7 plays a role in translation.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray analyses revealed that ectopic overexpression of GRP7 affects the steady-state abundance of a suite of cellular transcripts. Among those are circadian-regulated transcripts and transcripts influenced by abiotic and biotic stress (66). Because GRP7 interacts with translational machinery components it is likely that GRP7 plays a role in translation.…”
Section: Discussionmentioning
confidence: 99%
“…A mock immunoprecipitation was performed using Red fluorescent protein (RFP)-Trap® beads (Chromotek), hereafter called IP−. After extensive washing, coprecipitated RNAs were eluted with TriReagent from IP+ and IP− samples, respectively, and quantified in duplicates via qPCR essentially as described (43). In parallel, transcript levels were determined in RNA isolated from the extract (input).…”
Section: Methodsmentioning
confidence: 99%
“…ABH1/CBP80 and CBP20 contribute to the regulation of AS and preferentially affect AS of the first intron, particularly at the 59 splice site (Laubinger et al, 2008;Raczynska et al, 2010). The hnRNP-like At-GRP7 (for glycine-rich RNA binding protein 7) that is upregulated by cold and oxidative stress has also been associated with ABA responses (Carpenter et al, 1994;Cao et al, 2006;Kim et al, 2008;Schöning et al, 2008;Schmidt et al, 2010;Streitner et al, 2010). GRP7 regulates a number of AS events, in particular those involving alternative 59 splice sites.…”
Section: Function Of Sfs In Abiotic Stress Responsementioning
confidence: 99%
“…Misexpression of several splicing regulators alters flowering time (Lopato et al, 1999;Ali et al, 2007;Streitner et al, 2010;Zhang et al, 2011). Similarly, when transcriptome changes were monitored in Arabidopsis plants transferred from 16 to 25°C, leading to accelerated flowering via the ambient temperature pathway, RNA processing-related factors were enriched .…”
Section: Flowering Timementioning
confidence: 99%